Investigating the Association between Maternal Iron Supplementation and Neonatal Jaundice: Maternal Iron and Neonatal Jaundice - Bham, Shireen Qassim; Munaver, Sagheera Anjum; Akhter, Aliya Nasim; Shaheen, Najma (Pakistan Journal of Health Sciences, 2024)
Neonatal hyperbilirubinemia, being the most common cause of admission in the neonatal period, remains a global burden, especially in low- and middle-income nations. Addressing the mother's risk factors for neonatal jaundice was crucial for delivering better neonatal healthcare. One possible risk factor for neonatal hyperbilirubinemia is maternal iron supplementation. Objective: To analyze the effect of maternal iron supplementation as a risk factor for neonatal hyperbilirubinemia. Methods: In this prospective cohort study, using convenience sampling women with prenatal appointments during the first trimester of their pregnancies were evaluated and placed on therapeutic and prophylactic iron supplementation. Women were grouped on basis of serum ferritin level. Injectable Iron were given to women not improving with oral iron. The primary outcome was proportion of neonates developing hyperbilirubinemia during the first week of life. Data analysis was done using SPSS version 23.0. Normality of the data was checked by Shapiro-Wilk test. Chi-squared test was applied to compare variables between groups. Regression analysis was conducted to find the association between maternal iron supplementation and neonatal hyperbilirubinemia. Results: A sample of 176 mothers participated in the study. The overall frequency of newborn hyperbilirubinemia was 50.6%. The odds of having hyperbilirubinemia were 5.5 times higher with injectable iron. (aOR 5.5 95%CI:1.36-22.33). Conclusion: The outcome highlighted the potential connection between the iron supplementation of the mother during pregnancy and the development of neonatal jaundice suggesting the need to exercise early intervention in pregnant mothers who were at high risk of newborn jaundice